Search activity in Google as an indicator of interest in the issue of climate change in cities : Pretraživanja u Googleu kao pokazatelj interesa za problem klimatskih promjena u gradovima - Tikunov, Vladimir (Array, 2020)
Growing climate threats require adequate action from the world community and individual countries. Therefore, today it is extremely important for international and national sustainable development policies to obtain reliable data on the attitude of the public in different countries to the issue of climate change. An increase in the level of awareness of the world's population regarding climate change may be used as a reliable indicator of this issue. A promising tool for studying it is the Google Trends search query counting service. The article presents a comparative analysis of interest in climate change in the cities of the world and actual climate variability in these cities. To illustrate the processes of climate change, the temperature variability ratings for the largest cities of the world and Russia for a period of 36 years between 1980 are 2016 are given. It is shown that for Russia, climate problems become more urgent with the occurrence of significant negative consequences. Climate issues are becoming more important for Russia, but the awareness of significant negative consequences is negligible. As a result, there is a low correlation between global search and temperature trends.